The Pull-Out Reparation Technique For Ulnar Collateral Ligament (UCL) Of The Thumb - Mitrović, Mihajlo (Halo 194 Scientific Journal of Emergency Medicine, 2020)
AbstractIntroduction: Ulnar collateral ligament (UCL) of the thumb injury is a very common injury. However, due to the complexity of the ligament anatomy, the inexperience of doctors and unavailability of diagnostic procedures, the ulnar collateral ligament of the thumb injury is most commonly overseen. The consequences are loss of thumb function, instability and pain in the metacarpophalangeal joint. For these precise reasons, there is a clear consensus that this injury should be treated operatively.Objective: The objective of this paper is to present the results of the pull-out technique for reconstructing the UCL ligament.Methodology:In between 2018 and 2020, we have operated on 11 patients with the UCL of the thumb rupture in our department. We approached the dorsoulnar side of the MCP joint of the thumb using the standard lazy S incision. In 9 out of 11 patients, a Stener ligament lesion was discovered. All patients had their ligament reconstructed using the pull-out technique, where the ligament was sewn through, then guided through a channel created using a K needle on the radial side of the base of the thumb. Results:The patients returned for re-evaluation 6, 12 and 24 weeks after surgery. Upon 24 weeks, the patients had no complaints regarding their thumb, they had full grip strength and could perform all the various grips. Two of the patients had a limited abduction amplitude of the thumb in the MCP joint. Conclusion: The pull-out technique is a safe and cheap operative technique for UCL of the thumb reconstruction.
Keywords: Keywords: UCL of the thumb, Stener lesion, pull-out technique